ASSESSING THAI NURSING COLLEGE STUDENTS’ SPEAKING ABILITY THROUGH THE PERSPECTIVES OF THEIR INDONESIAN COUNTERPARTS - Anggoro, Sapto Dwi (Universitas Hamzanwadi, 2020)
AbstractAssessing Thai Nursing College Students? Speaking Ability Through The Perspectives of Their Indonesian Counterparts The need for improving speaking skills is inevitable in some areas of majors. Nursing students are expected to have a good command of English due to the available opportunities to work abroad. The existence of an academic exchange program could be viewed as one of the alternative learning activities that may fit the needs of the learning experience for EFL students. This study was a qualitative research that aimed at finding communication problems encountered by Indonesian nursing students in their interactions with their counterparts during the academic exchange program held in a nursing college in Thailand. The results of the study showed that the communication problems encountered by Indonesian nursing students due to Thai students speaking ability were in terms of mispronunciations, incorrect word choices, and grammatical errors. Subsequently, it was also found that Thai nursing students used several strategies to cope with their speaking problems by asking for assistance, miming, and making repetition. This research eventually suggests a number of recommendations for students to 1). avoid using their first language even though they communicate with their own friends in the group. 2). share as much information as possible to activate their speaking strategies. 3). have self-confidence in all interactions with TNS. 4). avoid unnecessary jokes, mocking TNS due to different cultural values. Subsequently, a number of activities prior to the academic exchange should also be conducted in terms of 1). practices in formulating questions, 2.) introduction to Thai culture, 3). Introduction to Thai spoken English.